Psychologie im Nationalsozialismus - Graumann, Carl F. 1923-2007 (Springer, 1985)
Carl-Friedrich Graumann (Hrsg.): "Psychologie im Nationalsozialismus". Springer Verlag, Berlin, Heidelberg 1985, 325 S., Abb., br., 24,80 DM